Raising Awareness of False Positive Newborn Screening Results Arising from Pivalate-Containing Creams and Antibiotics in Europe When Screening for Isovaleric Acidaemia - James R. Bonham; Rachel S. Carling; Martin Lindner; Leifur Franzson; Rolf Zetterstrom; Francois Boemer; Roberto Cerone; Francois Eyskens; Laura Vilarinho; David M. Hougaard; Peter C.J.I. Schielen (MDPI AG, 2018)
While the early and asymptomatic recognition of treatable conditions offered by newborn screening confers clear health benefits for the affected child, the clinical referral of patients with screen positive results can cause significant harm for some families. The use of pivalate-containing antibiotics and more recently the inclusion of neopentanoate as a component within moisturising creams used as nipple balms by nursing mothers can result in a significant number of false positive results when screening for isovaleric acidaemia (IVA) by measuring C5 acylcarnitine. A recent survey conducted within centres from nine countries indicated that this form of contamination had been or was a significant confounding factor in the detection of IVA in seven of the nine who responded. In three of these seven the prominent cause was believed to derive from the use of moisturising creams and in another three from antibiotics containing pivalate; one country reported that the cause was mixed. As a result, four of these seven centres routinely perform second tier testing to resolve C5 isobars when an initial C5 result is elevated, and a fifth is considering making this change within their national programme. The use of creams containing neopentanoate by nursing mothers and evolving patterns in the prescription of pivalate-containing antibiotics during pregnancy require those involved in the design and operation of newborn screening programmes used to detect IVA and the doctors who receive clinical referrals from these programmes to maintain an awareness of the potential impact of this form of interference on patient results.